1990
DOI: 10.1099/00222615-32-2-87
|View full text |Cite
|
Sign up to set email alerts
|

Uses and limitations in the demonstration of specific circulating immune complexes in patients with amoebiasis

Abstract: Summary.A micro-enzyme linked immuaosorbent assay (micro-ELISA) has been evaluated as a diagnostic test to detect amoebic antigen in polyethylene glycol (PEG) precipitated circulating immune complexes (CIC) in sera from patients with amoebiasis. The immune complexes were captured on rabbit anti-amoebic IgGcoated wells of microtitration plates and the complexed antigen was detected by enzyme linked antihuman immunoglobulins. A titre of > 160 for the immune complexes was considered to be of clinical significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The CICs were prepared by the method as described elsewhere [17]. The optimal dilutions of IgG antibodies and PEG-precipitated CICs were determined by checker-board titration in a micro-ELISA.…”
Section: Sandwich Micro-elisa For Detection Of Cics In Peg-precipitatmentioning
confidence: 99%
“…The CICs were prepared by the method as described elsewhere [17]. The optimal dilutions of IgG antibodies and PEG-precipitated CICs were determined by checker-board titration in a micro-ELISA.…”
Section: Sandwich Micro-elisa For Detection Of Cics In Peg-precipitatmentioning
confidence: 99%
“…There seems to be some degree of protection that develops after invasive amebiasis, since recurrence of amebic liver abscess is very rare. Antibody titers in these patients remain high for months after recovery of the amebic episode, but circulating immune complexes tend to decline or disappear 3-6 months following completion of therapy [32,33,43,100].…”
Section: Membrane Composition and Surface Markersmentioning
confidence: 99%
“…To st,ldy the role of the immune response in the rejection of amebic infection, it is necessary to identify the antigens that elicit a humeral response and determine if they are important in protection. Several authors have analysed the main antigens recognized by sera from patients with invasive amebiasis [3,5,22,28,34,45,49,61,72,80,85,100]. It has been reported that the number of antigens is larger and the level of immunogenicity higher in cytoplasmic vesicles than in the plasma membrane [95].…”
Section: Membrane Composition and Surface Markersmentioning
confidence: 99%